Efficient markets, managerial power, and CEO compensation - Michael L. Bognanno (IZA World of Labor, 2019)
The escalation in chief executive officer (CEO) pay over recent decades, both in absolute terms and in relation to the earnings of production workers, has generated considerable attention. The pay of top executives has grown noticeably in relation to overall firm profitability. The pay gap between CEOs in the US and those in other developed countries narrowed substantially during the 2000s, making top executive pay an international concern. Researchers have taken positions on both sides of the debate over whether the level of CEO pay is economically justified or is the result of managerial power.
Keywords: J31; M52; 330; top executive pay; CEO compensation